A study on packet scheduling algorithms for healthcare contents over fifth generation (5G) mobile cellular network - Mohd Ramli, Huda Adibah (Electronics and Telecommunications Committee of Polish Academy of Sciences, 2020)
This paper models the downlink Fifth Generation (5G) network that supports a flexible frame structure and a shorter Round-Trip Time (RTT) for Hybrid Automatic Repeat Request (HARQ). Moreover, the design of the renowned Time Division Multiple Access (TDMA) packet scheduling algorithms is revised to allow these algorithms to support packet scheduling in the downlink 5G. Simulation results demonstrate that the Proportional Fair provides a comparable performance to the delay–aware Maximum-Largest Weighted Delay First for simultaneously providing the desired transmission reliability of the Guaranteed Bit Rate (GBR) and Non-Guaranteed Bit Rate (Non-GBR) healthcare contents whilst maximizing the downlink 5G performance.